Pengembangan Sistem Informasi Manajemen Penjualan UMKM Cokelat Mesuji Kota Batu - Achmad Raiz Sikrillah; Nurudin Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Cokelat Mesuji Batu is a Small and Medium Enterprises (SME) in the field of chocolate production and marketing located in Batu City, East Java Province. The management of SME needs to be managed with a good and correct system and management, including in the financial. Chocolate orders must use a pre-order system, therefore customers who want to order chocolate, first do the administration process before the production process. The problems with marketing management are promotions that do not reach the wider community by relying on social media such as Instagram and Facebook, the unaffordability of people who do not have an account on the media and the information submitted is not comprehensive. According to the above problems, the solution provided in solving it is the development of web-based management information systems. This web-based information system can reach people who do not use social media such as Facebook or Instagram. The software uses Javascript, NodeJS, ReactJS, MongoDB for its development, and BPMN (business process modelling notation) to describe its business flow. To ensure the system runs properly and correctly in the manufacture is done testing using a black box, white box for function testing, and compatibility to test the system can run in various browsers. The result of the test is that 100% of system functions can run and only on IE browsers that there are few major problems. In this testing phase, developers use several techniques including testing white box that is building a class of drivers to test several methods contained in the system, from the test results of the program code obtained the method of the function is by the expectations made by testers in the test case table. The black box test is to test the overall functional needs and obtained the results of all functions on the system is 100% declared valid according to the output. Compatibility testing is done by running the system in some browsers and there are only problems on the major site of the IE browser.